Determination of microscopic optical properties of agar and Zerdine phantoms at 635 nm using Kubelka-Munk function approach: a numerical study - Hüseyin Okan Durmuş; MirHasan Yu Seyidov (Institute of Advanced Engineering and Science, 2022)
Since the precise and accurate determination of the optical properties of materials is very important for the development and application of optical technology, the investigation of the optical properties of biological tissues with tissue-like phantoms is an important research field in the applications of lasers in medicine. In this study, after directly determining the macroscopic optical properties of the agar and Zerdine phantoms at 635 nm, including the absorbance, transmittance, reflectance, refractive index, and total attenuation coefficient with the single integrating sphere test apparatus; the microscopic optical characterization of these two different soft tissue phantoms were realized at 635 nm by using the Kubelka-Munk function approach. For this, the microscopic optical parameters, which are the absorption coefficient, scattering coefficient, reduced scattering coefficient, and penetration depth, were calculated over these determined macroscopic optical properties.